A Simple and Efficient Method of Extracting DNA from Aged Bones and Teeth. Issue 3 (14th December 2017) - Liu, Qiqi; Liu, Liyan; Zhang, Minli; Zhang, Qingzhen; Wang, Qiong; Ding, Xiaoran; Shao, Liting; Zhou, Zhe; Wang, Shengqi
Abstract: DNA is often difficult to extract from old bones and teeth due to low levels of DNA and high levels of degradation. This study established a simple yet efficient method for extracting DNA from 20 aged bones and teeth (approximately 60 years old). Based on the concentration and STR typing results, the new method of DNA extraction (OM) developed in this study was compared with the PrepFiler™ BTA Forensic DNA Extraction Kit (BM). The total amount of DNA extracted using the OM method was not significantly different from that extracted using the commercial kit ( p > 0.05). However, the number of STR loci detected was significantly higher in the samples processed using the OM method than using the BM method ( p < 0.05). This study aimed to establish a DNA extraction method for aged bones and teeth to improve the detection rate of STR typing and reduce costs compared to the BM technique.